2016
DOI: 10.1002/cyto.b.21390
|View full text |Cite
|
Sign up to set email alerts
|

Determination of blood cell subtype concentrations from frozen whole blood samples using TruCount beads

Abstract: Using this method whole-blood samples can be frozen using a simple preparation method, and stored long-term before accurate determination of cell concentration. This allows for standardized analysis of the samples at a reference laboratory in multi-center studies. © 2016 International Clinical Cytometry Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
16
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 16 publications
5
16
1
Order By: Relevance
“…Cryopreservation also provides further benefit in that biospecimens can be analyzed in large batches, minimizing overall analytical variability; this is especially important for studies in which collection occurs over a long period of time, or a large number of samples are obtained. Recently, we and others showed that cryopreserved peripheral blood, a biospecimen that is simple and inexpensive to prepare, is comparable to fresh blood for the enumeration of a number of leukocyte types, including monocytes, neutrophils, B‐lymphocytes, T‐cells, natural killer, and (NK)‐cells; our study also showed that these measures were also comparable to that obtained from cryopreserved peripheral blood mononuclear cells (PBMCs) or a hematology analyzer. However, many of these cell types, especially monocytes, T‐cells, and NK‐cells, are known to represent distinct groups of subsets that have specific roles in maintaining health and preventing disease.…”
supporting
confidence: 72%
“…Cryopreservation also provides further benefit in that biospecimens can be analyzed in large batches, minimizing overall analytical variability; this is especially important for studies in which collection occurs over a long period of time, or a large number of samples are obtained. Recently, we and others showed that cryopreserved peripheral blood, a biospecimen that is simple and inexpensive to prepare, is comparable to fresh blood for the enumeration of a number of leukocyte types, including monocytes, neutrophils, B‐lymphocytes, T‐cells, natural killer, and (NK)‐cells; our study also showed that these measures were also comparable to that obtained from cryopreserved peripheral blood mononuclear cells (PBMCs) or a hematology analyzer. However, many of these cell types, especially monocytes, T‐cells, and NK‐cells, are known to represent distinct groups of subsets that have specific roles in maintaining health and preventing disease.…”
supporting
confidence: 72%
“…Of the two previous studies (16,17) that also compared absolute counts between fresh and cryopreserved blood, one also found these estimates to be significantly lower in cryopreserved blood, albeit to a lesser extent than our findings (17). We observed a significant discrepancy between absolute counts from fresh and cryopreserved blood, which was far less dramatic for estimates relative to CD45 and almost non-existent for estimates relative to PBMCs.…”
Section: Cytometry Part B: Clinical Cytometrycontrasting
confidence: 59%
“…Based on previous reports (16,21), we suspected that the cell washing step employed following staining, fixation and lysis might be the culprit. Based on previous reports (16,21), we suspected that the cell washing step employed following staining, fixation and lysis might be the culprit.…”
Section: Washing Following Staining Fixation and Lysis Of Cryopresermentioning
confidence: 96%
See 2 more Smart Citations